Support for smoke-free policy, and awareness of tobacco health effects and use of smoking cessation therapy in a developing country - McNeill Ann; Lewis Sarah; Owusu-Dabo Ellis; Gilmore Anna; Britton John (BMC, 2011)
Abstract Background Preventing an epidemic increase in smoking prevalence is a major challenge for developing countries. Ghana, has maintained a low smoking prevalence despite the presence of cigarette manufacturing for many decades. Some of this success may have been contributed by cultural factors and attitudes. We have studied public awareness of health risks, attitudes to smoke-free policy, tobacco advertising/promotion and other factors in a Ghanaian population sample. Methods We used two-stage cluster randomized sampling to study household members aged 14 and over in a representative household sample in the Ashanti Region of Ghana. Results 6258 people, 88% of those eligible, took part in the study. Knowledge of health risks of smoking and passive smoking was high; radio was the main source of such information. Most people work and/or spend time in places where smoking is permitted. There was very strong support (97%) for comprehensive smoke-free legislation, particularly among Christians and Muslims. Despite the advertising ban, a third of respondents (35%), particularly in urban areas, had noticed advertising of tobacco or tobacco products, on the radio (72%) and television (28%). Among smokers, 76% had attempted to quit in the last 6 months, with the main sources of advice being friends and spouses. Use of nicotine replacement therapy was very rare. Low levels of health awareness were seen in females compared with males (Adjusted Odds Ratio (AOR); 0.51, 95% CI 0.39-0.69, p < 0.001). High levels of health awareness was seen among Traditionalists compared with Christians AOR; 2.16 95% CI 0.79-5.94, p < 0.05) and the relatively well educated (AOR; 1.70 95% CI 1.12-2.58, p < 0.05) and those living in rural areas (AOR 1.46 95% CI 1.14-1.87, p = 0.004). Conclusion Awareness of health risks and support for smoke-free policy are high in Ghana. Exposure to tobacco advertising or promotion is limited and most smokers have tried to quit. Whether these findings are cause or effect of current low smoking prevalence is uncertain.